Rancang Bangun Aplikasi Presensi Guru Otomatis dengan Menggunakan Teknologi Radio Frequency Identification (RFID) - Deyasmei Maulud Huda; Sulidar Fitri; Sarmidi Sarmidi (Computer Journal, 2025)
Teacher attendance recording at MTs Darussalam still relies on manual methods prone to delays, recording errors, and administrative inefficiency. This research develops an automated attendance system using Radio Frequency Identification (RFID) technology as a solution to these problems. The designed system enables attendance recording through identification card detection on reader devices, producing direct and accurate attendance documentation. Integration of ESP32 microcontroller with web-based applications forms the core of the system, ensuring centralized and easily accessible attendance data management. Functional testing demonstrates the system's success in executing all planned features. Implementation of the RFID attendance system has potential to enhance discipline, accelerate administrative processes, and promote school management digitalization. Research findings indicate that teacher attendance automation through RFID technology represents a viable alternative to replace manual systems.